Harmonizing Society: Bediuzzaman Said Nursi's Vision of Islamic Politics - Huringiin, Nabila; Hutama Al-Faruqi, Achmad Reza; Sayyidul Bachr, Achmad Wildan (Fakultas Dakwah Institut Agama Islam Sunan Giri Ponorogo, 2023)
Contemporary politics has given rise to various humanitarian disasters. The political world seems too preoccupied with personal, group, and factional power interests. One tangible impact is the destruction of social stability. In contrast, Islamic politics ontologically views human beings holistically and universally, and then epistemologically derives from the Revelation of Almighty God and the Sunnah of His Messenger. History has proven that Islamic politics has contributed significantly to social harmony in a civilization. Based on the aforementioned political paradigm, the question is how Said Nursi addresses these issues by applying his political principles. This research aims to uncover and explain the definition, purpose, politics, and solutions to contemporary political problems according to Bediuzzaman Said Nursi. Said Nursi's political principles play a crucial role in the modern political world, especially concerning issues of social harmony. The researcher employs a qualitative method and an Islamic political approach, using narrative data rather than numerical data. This research discovers that the Islamic political thought of Bediuzzaman Said Nursi holds a concrete vision in harmonizing society.